Optimization and test for structural parameters of UAV spraying rotary cup atomizer - Qingqing, Zhou; Xinyu, Xue; Weicai, Qin; Chen, Cai; Liangfu, Zhou (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Small unmanned aerial vehicle (UAV) pesticide application technology is developing rapidly in China. However, the spray efficiency of UAV sprayer is not stable, one important reason is that the lack of specialized aviation nozzle. Rotary cup atomizer is not easily to be blocked and has broad application foreground in UAV spray. In order to obtain good spraying quality and narrow droplet spectrum aviation spraying centrifugal nozzle, the impacts of rotary cup atomizer structural parameters on atomization property were studied. In this research, a centrifugal atomization test device was designed, on which a frequency converter was used to adjust the rotary speed, and a return valve was used to stabilize the flow rate and pressure of spray liquid. The droplet volume medium diameter (VMD) and droplet spectrum relative width (SRW) were tested by using laser particle analyzer and particle analysis system. The analysis results of variance and quadratic regression orthogonal test were used to optimize the structural parameters of rotary cup atomizer. The influences of rotary cup atomizer structural parameters on atomization property, such as groove shape, diameter, teeth number, cone angle and height were evaluated and analyzed by conducting single-factor test. The results showed that: the best optimized rotary groove shape was square, diameter and teeth number had significant effects on droplet VMD and SRW, while cone angle had no effect on the droplet VMD and SRW, height affected droplet VMD but did not affect droplet SRW. Therefore, diameter and teeth number were selected as the variables of quadratic regression orthogonal test, droplet VMD and SRW regression model was established by using response surface analysis method. The optimized structural parameters respectively were: groove shape square, cone angle 60°, height 20 mm, diameter 61.5 mm and teeth number 149. Droplet VMD and SRW simulation value respectively were 200 μm and 0.562. The differences between simulation value and test value were 0.68% and 9.90% respectively, indicating that the regression model is accurate. The research result can provide a reference for further optimizing the structure parameters of rotary cup atomizer to meet the requirement of UAV spraying.Keywords: rotary cup atomizer, atomization, droplet VMD, droplet SRW, optimization, mathematical model, response surfaceDOI: 10.3965/j.ijabe.20171003.3119Citation: Zhou Q Q, Xue X Y, Qin W C, Cai C, Zhou L F. Optimization and test for structural parameters of UAV spraying rotary cup atomizer. Int J Agric & Biol Eng, 2017; 10(3): 78–86.